Characteristic Community Empowerment Transformation to Prevent Stunting - Fatma, Fatmawati Gaffar; Sardin, Sardin; Marzuki, Kartini; Amir, Rudi (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2025)
Stunting is a crucial health problem in Indonesia, especially in children under five years. Various factors influence this condition, including nutrition, economics, environment, and health. Empowering communities with character is an effective strategy to prevent stunting by actively involving the community in decision-making and program implementation. This article discusses the transformation of community empowerment with character to prevent stunting through a participatory approach, capacity building, and culture-based interventions. This study examines the transformation of community empowerment with character to prevent stunting. This study uses a qualitative method with a case study type. Data collection uses observation and interviews. Data are analyzed descriptively and qualitatively. The study results indicate that empowerment transformation is an approach to prevent stunting characterized by developing modules on nutrition, stakeholder involvement, and conducting evaluations for the sustainability of community empowerment. The impact of community empowerment transformation is that they have greater capacity to maintain the health and well-being of their children.